PENGARUH HERDING, PENDAPATAN DAN USIA TERHADAP KEPUTUSAN INVESTASI PADA EMAS - Lina Ani Safitri; Yanuar Rachmansyah D (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study aims to determine the effect of herding, income and age toward investment decision making. This research is quantitative research. Population in this study were people in the city of Semarang who invested gold in pawn shops The sample used in this study werw 100 samples. The sampling technique used is the random sampling. Data collection method used in this study is the questionnaire method. The analytical tool in this study is Multiple Linear Regression Analysis, Classic Assumption Test and Hypothesis Test using the SPSS 25 program. The results show that herding and age have a significant positive effect toward investment decision making, while income has no significant negative effect on investment decision making